Managing School Operational Assistance (BOS) Funds as a Practice of Social Change: A Phenomenological Study of Senior High Schools in Serang City through Giddens’ Structuration Theory" - Satibi, M; Reviyanti, Reviyanti; Riswanda , Farel Kyla; Dudayef, Faisal (Journal of Applied Business, Taxation and Economics Research, 2026)
This paper investigates the management of School Operational Assistance (BOS) funds as a manifestation of social change management within Senior High Schools (SMU) in Serang City, utilizing the theoretical framework of Anthony Giddens’ Structuration Theory. Utilizing a qualitative Interpretative Phenomenological Analysis (IPA) design, the study drew upon semi-structured in-depth interviews, non-participatory observations, and document analysis of key school actors—principals, treasurers, teachers, and school committees—directly involved in fund administration. Through a rigorous analysis involving initial noting, emergent theme identification, and superordinate theme clustering based on reflective interpretation, four core themes emerged: (1) accountability as a formal obligation; (2) the structural dominance of policy in management practices; (3) agency negotiation amidst structural constraints; and (4) fund management as a vehicle for social change. The findings underscore that while BOS policy structures constrain school actors, they simultaneously shape action patterns, allowing actors to exercise reflective capacity and negotiate practices within their local contexts. By integrating Structuration Theory with interpretive phenomenology, this research contributes to educational management literature, specifically illuminating the "duality of structure" in public fund management. The study advocates for policy shifts toward more reflective and contextual BOS management, emphasizing the capacity building of school actors to ensure accountable and sustainable education governance.